Alloys for Hot Dip Galvanising on Thin-Walled Materials - Żabiński, Piotr; Leszczynska-Madej, Beata; Włoch, Grzegorz; Lewartowski, Piotr (Journal of Casting & Materials Engineering, 2024)
The article reviews alloy additives to zinc and their impact on the quality of coatings achieved on structural steel. It also analyses the impact of the concentration of acid used for the chemical stripping of raw material on the zinc coating thickness of the steel. The zinc layer thickness changed depending on the concentration of alloy elements in the bath. It was stated that aluminium and bismuth have a low impact on the decrease in zinc coating thickness, while in the case of tin, a small change to the content (from 0.6% to 0.8%) significantly decreased the zinc layer thickness. Furthermore, it was found that, during the hot dip galvanising of steel, particular alloy elements are extracted from the bath. This results in the need to supplement alloy elements through periodical melting in for the purpose of maintaining the assumed bath composition. It was observed that, together with the increase in alloy elements concentration, zinc uptake (galvanised component weight ratio to black component weight) decreases, improving the process economics.